2005
DOI: 10.1080/014850190884318
|View full text |Cite
|
Sign up to set email alerts
|

Is Varicocele a Prognostic Factor for Determining Sperm Retrieval Rate Before Testicular Sperm Extraction?

Abstract: &66 nonobstructive azoospermic men with normal genetic analysis composed of 32 (48%) patients with and 34 (52%) patients without varicocele were evaluated for the rate of sperm extraction five months after the varicocelectomy. Sperm retrieval was successful in 22 of 32 patients (68%) who had been operated because of varicocele and in 13 of 34 patients (38.2%) who had no varicocele (OR ¼ 3.55) (CI: 1.15-11.27) (p ¼ 0.025). Overall, sperm extraction was successful in 35 of 66 patients (53%). Repair of varicocele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Interestingly, our findings did not show a significant impact of varicocele on the success of sperm retrieval in men with NOA. This is consistent with previous research that has shown inconsistent results regarding the effect of varicocele on sperm retrieval rates [ 41 ]. Despite the debate regarding the benefits of varicocelectomy in patients with NOA, some studies suggest that its repair may contribute to the reappearance of spermatozoa in semen, potentially improve testicular sperm recovery rate, enhance pregnancy rates in ICSI programs, and reduce the need for testosterone replacement therapy in cases of late-onset hypogonadism [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our findings did not show a significant impact of varicocele on the success of sperm retrieval in men with NOA. This is consistent with previous research that has shown inconsistent results regarding the effect of varicocele on sperm retrieval rates [ 41 ]. Despite the debate regarding the benefits of varicocelectomy in patients with NOA, some studies suggest that its repair may contribute to the reappearance of spermatozoa in semen, potentially improve testicular sperm recovery rate, enhance pregnancy rates in ICSI programs, and reduce the need for testosterone replacement therapy in cases of late-onset hypogonadism [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…The general opinion seems to suggest that there is no evidence that treatment of varicocele in men from couples with unexplained subfertility improves the couple's chance of conception (25,26). On the other hand, many other studies stated that varicocele repair, even of subclinical degrees, has a positive impact on spermatogenesis and subsequent pregnancy rates, whether through natural conception or assisted reproduction techniques (27)(28)(29)(30). The present study, however, shows that there are underlying molecular mechanisms that differ in varicocele patients compared with fertile individuals of the same age.…”
Section: Discussionmentioning
confidence: 95%